Visible policing: uniforms and the (re)construction of police occupational identity. (7th February 2023) - Rowe, Michael; Jones, Matthew; Millie, Andrew; Ralph, Liam
ABSTRACT: This article contributes to contemporary criminological debates on police visibility by exploring the relationship between police uniforms, artefacts and occupational identity. The article is influenced by visual criminology and semiotics and draws on elicitation interviews with officers and staff from four English police services. Participants were asked to bring with them an object or image that they identified as being an important expression of their occupational identity, which was then discussed. Most often objects or images were associated with their uniform. Findings are presented in relation to the visual symbolism, iconography and performativity of uniforms and related material artefacts. Participants drew upon visual representations in making sense of positive and negative aspects of their role and in defending their occupational identity in the light of perceived external challenges, such as reductions in police numbers and threats of violence and danger. It is argued that the communicative properties of this material culture play an important symbolic role in the self-legitimation and professional identity of police work.